2001
DOI: 10.1103/physrevd.64.054002
|View full text |Cite
|
Sign up to set email alerts
|

Virasoro constraints and flavor-topology duality in QCD

Abstract: We derive Virasoro constraints for the zero momentum part of the QCD-like partition functions in the sector of topological charge . The constraints depend on the topological charge only through the combination N f ϩ␤/2 where the value of the Dyson index ␤ is determined by the reality type of the fermions. This duality between flavor and topology is inherited by the small-mass expansion of the partition function and all spectral sum rules of inverse powers of the eigenvalues of the Dirac operator. For the speci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…In section 4.1 it is shown that results for the microscopic spectral density and microscopic spectral correlation functions obtained in this way are in exact agreement with previous results form Random Matrix Theory [2]. An exact calculation of the resolvent of the QCD 3 partition function from its finite volume partition function is thus possible by using the recent results for the QCD 4 finite volume partition function [31] (see section 4.2). In sections 5 and 6 we perform explicit calculations in QCD 3 based on the replica method.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…In section 4.1 it is shown that results for the microscopic spectral density and microscopic spectral correlation functions obtained in this way are in exact agreement with previous results form Random Matrix Theory [2]. An exact calculation of the resolvent of the QCD 3 partition function from its finite volume partition function is thus possible by using the recent results for the QCD 4 finite volume partition function [31] (see section 4.2). In sections 5 and 6 we perform explicit calculations in QCD 3 based on the replica method.…”
Section: Introductionsupporting
confidence: 72%
“…For non-integer values of ν we define the QCD 4 partition function according to the analytical continuation in ν of the Bessel functions [31], 9) and not by analytical continuation in ν of the unitary matrix integral (2.12). The integral (2.12) satisfies an important relation known as flavor-topology duality [38].…”
Section: The Qcd 3 Partition Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…At vanishing lattice spacing a the matrix D W has ν zero modes and n pairs of imaginary eigenvalues ±iy. This ensemble is known as the chiral Gaussian orthogonal ensemble [42,43,61]. For small lattice spacing |a| 1 we can apply first order perturbation theory.…”
Section: A Discussion Of the Partition Function At Finite Amentioning
confidence: 99%
“…which is expressed in terms of the partition function at a = 0, see [42,46]. This expression has some interesting relations to the microscopic partition function of the chiral Gaussian orthogonal random matrix ensemble (chGOE) which is up to a factor the same as the partition function Z N f ν (M + iσ, a = 0),…”
Section: A Chiral Lagrangian For the Fermionic Quarksmentioning
confidence: 99%